Studi Komparatif Terhadap Narasi Eksorsisme Roh Jahat Dalam Film The Nun I Sampai II dan Eksorsisme Yesus Dalam Markus 1:21-28 - Wijaya, Jonathan Cristian; Lo, Lemuel; Wahongan, Jesica (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Films featuring scenes of the expulsion of evil powers have been widely published to provide entertainment to the public, while also showcasing certain values within the narrative they visualize. One horror genre film that has garnered considerable interest is "The Nun I and II." These films depict the struggle of several priests attempting to expel the evil spirit named Valak. There are several scenes showing how the characters in the film beseech God for strength to defeat the dark power of Valak. The exorcism narrative depicted in these films offers several points of interest to be examined from a biblical perspective. Speaking of exorcism, the Gospel of Mark also presents several stories of exorcism performed by Jesus against evil spirits. This paper compares the exorcism narrative portrayed in "The Nun I and II" with the exorcism narrative performed by Jesus in the Gospel of Mark, as recounted in Mark 1:21-28. The purpose of the comparison presented in this paper is to demonstrate the relevance (similarities) and irrelevance (differences) of the concept of exorcism as portrayed in both "The Nun I and II" and Mark 1:21-28, enabling one to identify which points align and which do not align with the latter as one of the texts describing exorcism performed by Jesus.